Innsaei : heal, revive and reset with the Icelandic art of intuition - Gunnsteinsdóttir, Hrund, 1974- (HarperOne, an imprint of HarperCollinsPublishers, 2024)
"This eye-opening book is made up of personal stories from around the globe, including Hrund's own, wisdom from different cultures, science and the arts. Readers can keep a journal at hand to explore the exercises and savor in renewing our connection to our InnSæi. Throughout, Hrund offers us a potent toolkit which includes breathing and meditation exercises to re-engage our consciousness, grounding, mindfulness, and gratitude. This is for: Readers interested in burnout and balancing work-lifeReaders interested in spirituality and body, mind, and spirit contentIt is for spiritual seekers on a nontraditional path of enlightenment. With the many challenges that our generation faces, we have never needed the human superpowers of creativity, empathy, tolerance and open-mindedness so much as the present moment. We desperately need the vivid imagination of so many to create a sustainable and flourishing future for all. InnSæi is your inner guide, the voice of your soul"--